Root system and its relations with soil physical and chemical attributes in orange culture - Barbosa, Ronny Sobreira; de Souza, Zigomar Menezes; Carneiro, Marina Pedroso; Farhate, Camila Viana Vieira [UNESP] (MDPI, 2021)
Citrus companies have sought and developed alternative systems of tillage or implanting orchards so as not to significantly alter the physical and chemical attributes of the soil and, consequently, the root development of plants. Therefore, the aim of this study was to identify the physical and chemical attributes of the soil that most influence the root volume of the orange crop in different tillage systems. The experiment was carried out in the region of Avaré, state of São Paulo, Brazil, in Utissol and Oxisol. For the planting of the orange crop, the following tillages were made: minimum tillage, subsoiler tillage and soil tillage using a triple tillage implement. The physical and chemical attributes evaluated were bulk density, macroporosity, microporosity, total porosity, soil moisture, soil mean weight-diameter, soil resistance to penetration, sum of bases, cation exchange capacity, base saturation, pH, exchangeable cations, potential acidity, available phosphorus, analysis of mi-cronutrients such as copper, iron, manganese and zinc, and organic carbon content. The root system was evaluated using SIARCS® software. For data classification, data mining techniques were used such as attribute selection and decision tree induction. Regardless of the soil type, the use of the triple operation implement provided greater root volume for orange plants. For the Utisol area, the pH value of 4.2 was the main attribute that provided a high root volume. For the Oxisol, the presence of copper, in levels that did not generate toxicity for the plants, provided a high volume of root for the crop.
Keywords: Citrus sinensis; Data mining; Root volume; Soil tillage